Adult ADHD: Influence of Physical Activation, Stimulation, and Reward on Cognitive Performance and Symptoms. Issue 6 (April 2021) - Kallweit, Claudia; Paucke, Madlen; Strauß, Maria; Exner, Cornelia
Objective: Models of ADHD consider the influence of situational factors on cognitive performance and symptoms.Method: The influence of acute physical exercise, stimulation through continuous fine motor movement, and performance-related reward on performance and ADHD symptoms was assessed. Thirty-six adults with ADHD and 36 healthy controls performed executive function tasks (EF-tasks) of inhibition, selective attention, and working memory with material close to daily life. Experimental manipulations aimed at increasing cognitive performance.Results: No significant effects were found, but there were indicators for ADHD-specific impacts: Reward resulted in higher reported hyperactivity. Acute physical exercise slightly tended to improve attention performance and subjective inattention.Conclusion: The manipulations may affect performance and especially symptoms in different ways. Potential symptom interactions and identification of factors that determine whether symptoms may be functional or detrimental for task performance could be future research interests.